Justice Collaborator at a Legal Crossroads: An Analysis of the Tension between Substantive Justice and Legal Certainty - Firmansyah, Rizqy Adi; Widjaja, Matthew; Kusumawardani, Cesilia Elok; Sugianto, Fajar; Indradewi, Astrid Athina (SIGn Jurnal Hukum, 2025)
This research examines the tension between substantive justice and legal certainty within the Indonesian criminal justice system, which arises from the legal ambiguity surrounding the Justice Collaborator. The case study focuses on the Justice Collaborator verdict in the premeditated murder case involving Irjen FS. Utilizing a normative juridical research method through statute, case, and conceptual approaches, this study aims to analyze how the legal vacuum regarding the Justice Collaborator in the Penal Code is addressed through judicial adaptation. The findings indicate that the Panel of Judges constructed a “parallel penal track” to grant a reward to Bharada E as the Justice Collaborator. This track refers to sectoral legal instruments such as Law Number 13 of 2006 and Supreme Court Circular Number 4 of 2011. Although this practice successfully realized substantive justice, it inherently creates a systemic implication in the form of tension between judicial discretion and the principle of legal certainty, a pillar of the civil law system. It is concluded that the absence of a codified norm for the Justice Collaborator potentially threatens the consistency and predictability of criminal law, which, if not promptly addressed through reform, could risk the systemic delegitimization of the criminal justice system in the future. Therefore, this research recommends the urgent need for a comprehensive codification of the Justice Collaborator doctrine into the Penal Code and Law Number 8 of 1981 to align the needs of law enforcement with the maintenance of the principle of legality.